Pengaruh dan Efektivitas Penggunaan Media Digital LMS dalam Proses Pembelajaran - Andri Sahata Sitanggang; Bangkit Yofanka Manalu; Muhammad Anwar; Muhamad Bagas Nursoleh; Dwi Faiz Azhar Restiadi (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Digital transformation in the world of education has encouraged the use of digital media, particularly Learning Management Systems (LMS), in the learning process. This study aims to analyze the influence and effectiveness of LMS use on improving learning quality, learning motivation, and student engagement. The method used in this study is a Systematic Literature Review (SLR), analyzing ten relevant national scientific articles published within the past five years. The findings indicate that the use of LMS such as Google Classroom, Moodle, and Schoology generally contributes positively to supporting more interactive, flexible, and structured learning. LMS has also proven to enhance learning independence and facilitate learning management by educators. However, its effectiveness is influenced by human resource readiness, digital competencies, and the availability of technological infrastructure. Therefore, continuous training for educators, the selection of LMS tailored to specific needs, and infrastructure support are necessary to achieve effective and sustainable digital learning.